Action planning and affective states within the auditory peripersonal space in normal hearing and cochlear-implanted listeners. (14th May 2021) - Bahadori, Mehrdad; Barumerli, Roberto; Geronazzo, Michele; Cesari, Paola
Abstract: Fast reaction to approaching stimuli is vital for survival. When sounds enter the auditory peripersonal space (PPS), sounds perceived as being nearer elicit higher motor cortex activation. There is a close relationship between motor preparation and the perceptual components of sounds, particularly of highly arousing sounds. Here we compared the ability to recognize, evaluate, and react to affective stimuli entering the PPS between 20 normal-hearing (NH, 7 women) and 10 cochlear-implanted (CI, 3 women) subjects. The subjects were asked to quickly flex their arm in reaction to positive (P), negative (N), and neutral (Nu) affective sounds ending virtually at five distances from their body. Pre-motor reaction time (pm-RT) was detected via electromyography from the postural muscles to measure action anticipation at the sound-stopping distance; the sounds were also evaluated for their perceived level of valence and arousal. While both groups were able to localize sound distance, only the NH group modulated their pm-RT based on the perceived sound distance. Furthermore, when the sound carried no affective components, the pm-RT to the Nu sounds was shorter compared to the P and the N sounds for both groups. Only the NH group perceived the closer sounds as more arousing than the distant sounds, whereas both groups perceived sound valence similarly. Our findings underline the role of emotional states in action preparation and describe the perceptual components essential for prompt reaction to sounds approaching the peripersonal space. Highlights: Effect of approaching affective auditory stimuli in PPS on action preparation was investigated in NH and CI individuals. Further to premotor reaction times (pm-RTs), subjective auditory distance and emotional perception have been measured. Just NH modulated their pm-RTs based on the distance although both groups showed the ability of perceiving distance. Both groups reacted faster to neutral sounds. Only NH perceived the closer sounds more arousing than farther sounds. The results revealed the important role of arousal induced by the auditory stimuli within the PPS in action preparation.